2020
DOI: 10.1039/d0cc05532h
|View full text |Cite
|
Sign up to set email alerts
|

Controlling receptor function from the extracellular vestibule of G-protein coupled receptors

Abstract: Receptor function is traditionally controlled from the orthosteric binding site of G-protein coupled receptors. Here, we show that the functional activity and signalling of human dopamine D2 and D3 receptor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…The antagonistic behaviour of 59 was also preserved in the β-arrestin signalling pathway; following the previous trends introduction of any SP led to an increase in pIC 50 values here as well. In general, the efficacy data measured at both receptors followed similar trends in both modalities as the receptor affinities ( Egyed et al, 2020 ).…”
Section: Bitopic Ligands To Study Selectivity and Functional Selectiv...mentioning
confidence: 77%
See 3 more Smart Citations
“…The antagonistic behaviour of 59 was also preserved in the β-arrestin signalling pathway; following the previous trends introduction of any SP led to an increase in pIC 50 values here as well. In general, the efficacy data measured at both receptors followed similar trends in both modalities as the receptor affinities ( Egyed et al, 2020 ).…”
Section: Bitopic Ligands To Study Selectivity and Functional Selectiv...mentioning
confidence: 77%
“…Commun. 2020, 56 (91), 14167–14170) ( Egyed et al, 2020 ). (C) The binding mode of salbutamol (cyan) and salmeterol (green) ( Masureel et al, 2018 ) in the β 2 R highlighting the important role of ECL2 as discussed in more detail in the binding kinetic section of this review.…”
Section: Ligand Binding Pocket Revealed By Experimental Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“… 27 30 Recently, the field of bitopic ligands has been expanded to other protein classes including kinases, e.g., mTor 31 and PKCα, 32 and a merged bitopic ligand for the nuclear receptor PPARγ. 33 These chemical biology studies have demonstrated that a dual targeting strategy is associated with several advantages over monovalent targeting strategies, including an increased affinity 30 , 34 or selectivity, 30 , 34 36 a bias in signaling pathway activation, 30 , 37 and reduced therapeutic resistance. 31 …”
Section: Introductionmentioning
confidence: 99%